Tour 13: From Precarity to Ephemerality. Issue 2 (2nd July 2016) - Bruce, Caitlin Frances
Abstract : This article explores a temporary street art project in Paris's 13th arrondissement, Tour 13. The project, which involved more than 100 street artists taking over abandoned apartments and transforming them, to be displayed for a one-month period before the building was demolished, draws attention to the rhythms of creative destruction that underlie urban renewal practices. Moreover, the process of waiting to enter the building and the works contained within function to draw attention to both the losses caused by precarious economies and the need for an alternative social temporal framework, one more focused on ephemerality. Bridging recent discussions in cultural studies, rhetoric, and critical urban studies, this article explores the politics of precarity and the creative class as it effectuates built space in Paris and argues that ephemerality offers an alternative temporal and political response to precarity.